Darwin’s Church - White, Paul (Studies in church history, 2010)
From the war of nature, from famine and death … endless forms most beautiful and most wonderful have been, and are being, evolved.(Charles Darwin, On the Origin of Species)Much has been made of the roots of Darwinian theory in the work of Thomas Malthus, who argued for the inevitability of strife, suffering and death following on the scarcity of resources and the tendency of populations to multiply without limit. It has been noted that a Malthusian pessimism about human nature re-emerged in the 1830s, darkening the political discussions surrounding the welfare of the poor, and informing the legislation of the Poor Laws in those crucial years in which Darwin formulated his natural selection theory. Historians have also focussed on the harshness of the social Darwinism that was taken up by theorists later in the century, in contrast to the more optimistic, Lamarckian evolution of Herbert Spencer, Peter Kropotkin and others. Yet in the closing passage of Origin of Species, Darwin extended his famous metaphor of the entangled bank, offering a form of redemption through struggle toward higher forms of life.